2018
DOI: 10.1021/jacs.8b00178
|View full text |Cite
|
Sign up to set email alerts
|

Palladium/PC-Phos-Catalyzed Enantioselective Arylation of General Sulfenate Anions: Scope and Synthetic Applications

Abstract: Herein we reported an efficient palladium-catalyzed enantioselective arylation of both alkyl and aryl sulfenate anions to deliver various chiral sulfoxides in good yields (up to 98%) with excellent enantioselectivities (up to 99% ee) by the use of our developed chiral O,P-ligands (PC-Phos). PC-Phos are easily prepared in short steps from inexpensive commercially available starting materials. The single-crystal structure of the PC4/PdCl showed that a rarely observed 11-membered ring was formed via the O,P-coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 125 publications
(47 citation statements)
references
References 61 publications
(14 reference statements)
1
44
0
2
Order By: Relevance
“…232 A more general and robust approach for the enantioselective arylation of general sulfenate anions was recently reported by Zhang and co-workers, using a XantPhos-derived PC-Phos ligand (Scheme 65b). 233 Additionally, Tan and co-workers disclosed an organocatalytic approach for the enantioselective alkylation of sulfenate anions generated from sulfoxides, using halogenated pentanidium salts as phase-transfer catalysts. 234…”
Section: Sulfoxidesmentioning
confidence: 99%
“…232 A more general and robust approach for the enantioselective arylation of general sulfenate anions was recently reported by Zhang and co-workers, using a XantPhos-derived PC-Phos ligand (Scheme 65b). 233 Additionally, Tan and co-workers disclosed an organocatalytic approach for the enantioselective alkylation of sulfenate anions generated from sulfoxides, using halogenated pentanidium salts as phase-transfer catalysts. 234…”
Section: Sulfoxidesmentioning
confidence: 99%
“…2‐(Dodecylsulfinyl)‐1,3,5‐trimethylbenzene (4 al) : R f =0.25 (5% ethyl acetate/hexane); Colourless liquid; yield 66% (56 mg); 1 H NMR (400 MHz, CDCl 3 ) δ 6.85 (s, 2H), 3.29–3.19 (m, 1H), 2.85–2.76 (m, 1H), 2.53 (s, 6H), 2.28 (s, 3H), 1.85–1.71 (m, 1H), 1.70–1.61 (m, 2H), 1.51–1.38 (m, 2H), 1.35–1.26 (m, 5H), 1.25–1.23 (s, 10H), 0.87 (t, J =6.8 Hz, 3H); 13 C NMR (100 MHz, CDCl 3 ) δ 141.1, 138.5, 135.2, 131.0, 52.6, 32.0, 29.7, 29.7 (x2), 29.5, 29.4, 29.3, 28.9, 23.9, 22.8, 21.2, 19.4, 14.3.…”
Section: Methodsmentioning
confidence: 99%
“…A series of commercially or readily available chiral ligands were systematically investigated, and our developed chiral sulfinamidephosphine‐type ligands delivered 3 a in up to 90 % yield and up to 75 % ee (see Figure S1 in the Supporting Information). Further screening showed that PC‐Phos could give relatively higher ee values (Table ). For example, ( Sc , Rs )‐ PC3 gave 3 a in 91 % yield with 92 % ee (entry 3).…”
Section: Figurementioning
confidence: 99%